Secrets of Thomas Hardy’s Biography: The Attempt of Reading in John Fowles’ Works - Levytska, Oksana (Pitannâ lìteraturoznavstva, 2014)
Hardy’s personality as a writer and a man invariably accompanies John Fowles’ texts, he repeatedly clearly and sometimes with hints and allusions appeals to the creativity of this outstanding writer of the Victorian era, uses as an epigraph quotes from his texts, reveals little known facts of his biography, conducts the biographical analysis of his works, etc. John Fowles’ permanent appeal to Thomas Hardy’s personality the author himself explains by close proximity and affinity of writer’s work. On the material of essays by John Fowles (“Hardy and the Hag”, “Thomas Hardy’s England”) and the novel “The French Lieutenant’s Woman” is analyzed Fowles’ appeal to the biographical method of analysis of literary works. The writer’s opinions regarding methodologies of literature of the second half of the twentieth century with their formal search and the benefits of the appeal to biographism are found out. The features of biographical study of Thomas Hardy’s personality are analized in Fowles’ works, focus is made on the explaination of the characteristics of the English mentality, the use of the background in connection with the real historical time, the illustration of the writer’s complexes and so on. Special attention is paid to Hardy’s family mysteries as the illustrations of the dual nature of the Victorian epoch, and the key to the interpretation of the mental processes of creativity and the analysis of the novel “Beloved”. The identity of Thomas Hardy in Fowles’ works is the illustration of Englishness, an attempt to explain the peculiarities of the English mentality, creativity and attitude to their own publicity and vice versa – an expression of secrecy, isolation, and separation. The minutiae of Thomas Hardy’s biography, the details of his personal life John Fowles uses as a narration of customs and peculiarities of the Victorian era in his novel “The French Lieutenant’s Woman”. The usage of biohraphism is the way of connecting conditional and specific, real and fictional, Hardy’s biography in Fowles’ novel is also the documentary text, the evidence of the era and the artistic reinterpretation of mysteries of writer’s personality.